ROS: Trichothecenes' handy weapon?. (August 2020) - Ren, Zhihua; He, Hongyi; Zuo, Zhicai; Xu, Zhiwen; Wei, Zhanyong; Deng, Junliang
Abstract: Trichothecenes are a class of toxic secondary metabolites produced by filamentous fungi such as Fusarium, which pose a threat to human and animal health. Among them, T-2 toxin and deoxynivalenol (DON) have attracted the most attention because of their extensive pollution and strong toxicity. Accumulated studies have found that an increase of reactive oxygen species (ROS) during oxidative stress produces a wide range of secondary consequences by modifying cell signaling proteins, such as DNA RNA damage, inflammatory damage, cell cycle arrest, and apoptosis. Although there has been a comprehensive review of antioxidant agents against trichothecenes, there is no systematic summary of the mechanism of trichothecenes inducing ROS production and then regulating downstream signaling molecules of cells to produce the corresponding effects. Therefore, from the perspective of ROS regulation of downstream signaling pathways, this review mainly explores the mechanisms by which ROS, as trichothecenes' handy weapon, affect an organism. It may provide more ideas and new targets for studies of antagonizing the toxicity of trichothecenes from the aspect of antioxidation.